Menata Ulang Pembelajaran Atletik di Sekolah Dasar : Model Berbasis Permainan untuk Menumbuhkan Motivasi - Lukman Kharies Setyanto; Abdul Rachman Syam Tuasikal; Anung Priambodo (Jurnal Keolahragaan, 2026)
Motor, cognitive, and socio-emotional development among elementary school students may be adversely affected by low levels of physical activity. Physical Education, particularly athletics instruction, is often delivered in a monotonous manner, which can reduce students’ learning motivation. The effectiveness of a game-based athletics learning model in enhancing fifth-grade students' learning motivation at SDN Kepung 1, Kediri, was examined in this study. A quasi-experimental design was employed by assigning participants into an experimental group receiving the Formula One-Based Game intervention and a control group receiving conventional instruction. Data were collected using pretest and posttest questionnaires and were analyzed through normality testing, homogeneity testing, paired sample t-test, independent sample t-test, and N-Gain Score analysis to determine the effectiveness of the intervention. The experimental group showed a higher increase in learning motivation, with scores improving from 16.21 to 26.89, compared to the control group from 16.18 to 21.04. Furthermore, the N-Gain Score analysis indicated that the experimental group achieved a high effectiveness rate of 78.9%, whereas the control group scored 35.4%. The findings indicate that game-based learning enhances students’ learning motivation, active participation, collaboration, and meaningful learning experiences. This approach is recommended as an effective pedagogical strategy to foster elementary students’ intrinsic motivation in Physical Education.